Thresholds of hypoxia of two Red Sea coral species (Porites sp. and Galaxea fascicularis) - Alva García, Jacqueline V.; Klein, Shannon G.; Alamoudi, Taiba; Arossa, Silvia; Parry, Anieka J.; Steckbauer, Alexandra; Duarte, Carlos M. (Frontiers in Marine Science, 2022)
Anthropogenic pressures have driven large-scale declines in coral cover on >50% of tropical coral reefs. Most research efforts have focused on ocean warming, ocean acidification, and overfishing impacts. Despite increasing instances of reef-associated hypoxic events, the role of reduced O2 in affecting coral reef performance is largely unknown. Here, we assessed the hypoxic thresholds of two Red Sea coral species: Porites sp. and Galaxea fascicularis. We exposed coral fragments of both species to one control treatment (6.8 mg O2 L−1) and three reduced dissolved oxygen treatments (5.25, 3.5, and 1.25 mg O2 L−1) during a 10-day experiment. Across the two species, maximum (Fv/Fm) and effective (F′/Fm′) photochemical efficiency, chlorophyll a, and dark respiration declined under the lowest O2 treatment (1.25 mg O2 L−1). Porites sp. coral fragments, however, were remarkably resistant and showed no signs of sublethal bleaching after 10 days of exposure to reduced O2. Conversely, 17% of G. fascicularis fragments bleached after only three nights of exposure to the lowest O2 treatment (1.25 mg O2 L−1). Our data show that longer-term hypoxic events (i.e., days to weeks) can induce coral bleaching, but these effects depend on the extent of O2 reduction and are likely species-specific. Importantly, the levels of O2 usually defined as hypoxic (~2.0 to 2.8 mg O2 L−1) do not adequately capture the thresholds reported here. Hence, further research is urgently needed to more accurately describe the vulnerability of coral taxa to hypoxic and anoxic events.